Carbonates - Pastero, Linda (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue is aimed at presenting the state of the art of the multidisciplinary science concerning all aspects of volcanic plumes, of relevance to the volcanology, climatology, atmospheric science, and remote sensing communities.